Reconstructing SALMFamide Neuropeptide Precursor Evolution in the Phylum Echinodermata: Ophiuroid and Crinoid Sequence Data Provide New Insights - Elphick, Maurice R.; Semmens, Dean C.; Blowes, Liisa M.; Levine, Judith; Lowe, Christopher J.; Arnone, Maria I.; Clark, Melody S. (Frontiers in Endocrinology, 2015)
The SALMFamides are a family of neuropeptides that act as muscle relaxants in echinoderms. Analysis of genome/transcriptome sequence data from the sea urchin Strongylocentrotus purpuratus (Echinoidea), the sea cucumber Apostichopus japonicus (Holothuroidea) and the starfish Patiria miniata (Asteroidea) reveals that in each species there are two types of SALMFamide precursor: an L-type precursor comprising peptides with a C-terminal LxFamide-type motif and an F-type precursor solely or largely comprising peptides with a C-terminal FxFamide-type motif. Here we have identified transcripts encoding SALMFamide precursors in the brittle star Ophionotus victoriae (Ophiuroidea) and the feather star Antedon mediterranea (Crinoidea). We have also identified SALMFamide precursors in other species belonging to each of the five echinoderm classes. As in S. purpuratus, A. japonicus and P. miniata, in O. victoriae there is one L-type precursor and one F-type precursor. However, in A. mediterranea only a single SALMFamide precursor was found, comprising two peptides with a LxFamide-type motif, one with a FxFamide-type motif, five with a FxLamide-type motif and four with a LxLamide-type motif. As crinoids are basal to the Echinozoa (Holothuroidea + Echinoidea) and Asterozoa (Asteroidea + Ophiuroidea) in echinoderm phylogeny, one model of SALMFamide precursor evolution would be that ancestrally there was a single SALMFamide gene encoding a variety of SALMFamides (as in crinoids), which duplicated in a common ancestor of the Echinozoa and Asterozoa and then specialised to encode L-type SALMFamides or F-type SALMFamides. Alternatively, a second SALMFamide precursor may remain to be discovered or may have been lost in crinoids. Further insights will be obtained if SALMFamide receptors are identified, which would provide a molecular basis for experimental analysis of the functional significance of the “cocktails” of SALMFamides that exist in echinoderms.